Waste management techniques for improved environmental and public health : emerging research and opportunities - Tsai, Sang-Bing, 1973- (Advances in environmental engineering and green technologies (AEEGT) book series., 2020)
""This book provides insights into the advancing methods and technologies of reducing pollution and promoting sustainable development. It also examines ecological technologies, risk assessment, and green operation"--Provided by publisher"--